(untitled) (Global Journal of Management and Business Research, 2013)
Activity based costing (ABC) is a method for determining true costs; which has become an important aspect of manufacturing/service organizations and can be defined as a methodology that measures the cost and performance of activities, resources and cost objects. It can be considered as an alternative method to traditional cost accounting systems. In this paper we have shown a comparative analysis of application of ABC method with traditional cost accounting (TCA) method in an automobile parts manufacturing company; which would like to increase the sales due to increased demand. For this reason the company needs to know the true cost of the parts prior to deciding as which item is to be produced more.